Improving Students' Mathematical Communication Skills Through Learning Start Learning Models With A Question on Pythagoras - Nuraina, N; Mursalin, M (Universitas Malikussaleh, Aceh Utara, Indonesia, 2018)
This type of research is quasi-experimental. This study examines the Learning Start with a Question (LSQ) model in improving students' mathematical communication skills through the learning module. The population in this study were all students of mathematics education from the Teaching and Education Faculty, from semester V with the sample being students of class A1 and class A2. This study was divided into two learning groups, namely the experimental group by applying the Learning Start Learning Model with a Question (LSQ) and the control group with conventional learning. Based on the results of calculations using the t-test at the significance level Î± = 0.05 obtained a ttest of 4.64 with a significance value of 0.003, while the ttable of 1.76. Because tcount > ttable (4.64 > 1.76) and significance < 0.05 (0.003 < 0.05). It can be concluded that increasing students' mathematical communication skills by applying the Learning Start Learning Model with a Question (LSQ) and using the learning module is better than the mathematical communication skills of students who obtain conventional learning without learning modules.